Study of Old Plant Analysis on the Completion of ‘Pagang Gadai’ (Pawn) Agreement in Minangkabau Society - Farida Arianti; Asyari Hasan (Khazanah Sosial, 2022)
There had been a debt guarantee settlement completed in the Minangkabau community. The purpose of this study was to uncover how to understand about the utilization of debt guarantees in ‘Pagang Gadai’ (pawns), as well as the position of plant ownership on land repaid in pawn transactions. The method used was qualitative with a phenomenology approach. The data source of this research was people or communities (including indigenous figures) of Minangkabau customs who were involved in pawns transactions, especially in Nagari Tabek of Pariangan district. The data collection was conducted through in-depth interviews of five research informants based on interview guidance using snowball sampling technique.  The results showed that the use of pawns can be done with several conditions: 1) obtaining permission from the owner where there is no element of exploitation and managed by pawns, and 2) mastery of old plants can be done by the recipient of the pawn after redemption is classified to the exploitation that leads to take the property of others unjustly and blatantly (‘Ghasab’ behaviors).